Eliminating Production Process Waste with Lean Six Sigma in the Gresik Ceramic Industry - Pristyanto, Yafie; Rochmoeljati (Jurnal Sistem Cerdas, 2024)
The Gresik Ceramic Industry is a company operating in the ceramic industry. In the ceramic production area at PT XYZ, waste is still found, namely waste defects, safety health environment (SHE), excess processing. and motion. This research aims to identify and reduce waste in the ceramic production process using the Lean six sigma (LSS) method and Failure Mode Effect and Analysis (FMEA) as proposed recommendations for improvement. Lean six sigma uses 5 stages, namely define, measure, analyze, improve, control. However, research is carried out to the improvement stage to provide recommendations for improvement. The results of reducing the lead time value in the ceramic production process, which was originally 1880 minutes, changed to 1816 minutes or decreased by 64 minutes, thereby reducing the cycle time in the ceramic production process. Then the DPMO value obtained was13311 with a sigma level of 3.71. The research results show that crack defects have the highest RPN value of 576 with the cause being that the punches on the press machine have reached their useful life, causing the printing process to be less than perfect. The proposed recommendation for improvement is replacing the punches components on the press machine